Hormonal Influences on Tourette Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
A survey of 47 women with Tourette syndrome reported from the Section of Pediatric Neurology, Children's Hospital of Wisconsin, Milwaukee, WI had an increase in tics beginning at menarche and recurring premenstrually.